Cost-effectiveness of interventions for people with dementia without caregiver: A Systematic Review - Vu Thi, Hue; Bui Bich, Huong; Pham Hai, Thanh; Nguyen Huu, Thang (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: This study was conducted to answer the three questions: 1- What intervention with no caregiver to increase cost-effectiveness in patients with dementia have been implemented? 2- How has disease progression changed in these interventions? 3- How has cost effectiveness changed in these interventions? Methods: The databases were searched from PubMed, Cochrane and Science Direct. Studies on cost-effectiveness of interventions for people with dementia without caregiver published from 2010 to 2020 have been filtered. Systematic review was carried out according to the Cochrane Collaboration methodology. Search for documents based on PICOTS standards: Population - Patients with dementia, regardless of disease severity; Intervention - Intervention with no-caregiver for dementia patients; Comparison - The intervention group and the control group; Outcome measure - Disease progression and Cost effectiveness; Time - Studies published from January to January 2020. Study design: A randomized controlled trial. Study subjects are not age restricted. Results: 2163 documents were found, of which, there are 15 documents satisfy the criteria. (1) Modes of intervention: There are 3 studies on exercise interventions, 2 studies on drug treatment, the rest are different treatment programs. In which, the START program has done the most studies with 3 studies. (2) Disease progression: Out of the 15 studies, 14 found the difference between the intervention group and the control group. The intervention group mostly had higher QALYs and had better disease progression. (3) Cost-effectiveness: There are 11 out of 15 studies showing the cost-effectiveness of the intervention group compared with the usual care group. 4 remaining studies did not show a cost-effectiveness and there is no evidence of cost-effectiveness unless the service user is willing to pay certain amount for that intervention. Conclusion: This study shows evidence of no-caregiver interventions that improve dementia and increase the cost-effectiveness of treatment.